INCIDENCE OF MAXILLARY SINUSITIS AFTER MAXILLARY SINUS TRAUMA AT CAN THO CENTRAL GENERAL HOSPITAL IN 2023-2025 - Huynh, Thanh Dat; Vo, Thi Ngoc Han; Trang, Hong Hanh (Cantho Journal of Medicine and Pharmacy, 2025)
Background: The maxillary sinus is an empty, shallow bony cavity located in the middle craniofacial region, making it vulnerable to injury following trauma. When the maxillary sinus is injured, it can lead to various functional and aesthetic sequelae. One of the most common complications following maxillary sinus trauma is maxillary sinusitis, typically caused by edema, blood, residual bone fragments, soft tissue remnants, or foreign objects. Prevention and early treatment of maxillary sinusitis following trauma have received limited attention. Objective: 1) To determine the incidence of maxillary sinusitis following maxillary sinus trauma. 2) To describe the clinical, paraclinical characteristics, and treatment outcomes of maxillary sinusitis following maxillary sinus trauma. Materials and method: A cross-sectional descriptive study was conducted on 95 patients diagnosed with maxillary sinus trauma and treated at Can Tho Central General Hospital from March 2023 to March 2025. Results: The median age of the patients was 31 years (16-74 years), with a male-to-female ratio of 3:1. The main cause of trauma was traffic accidents, accounting for 93.7%. Most patients presented to the hospital within 6 hours to 10 days after the trauma (82.1%). Isolated maxillary sinus fractures were rare (5.3%), while maxillary sinus trauma with zygomatic bone fractures accounted for 54.7%, and maxillary sinus trauma with nasal bone fractures made up 36.8%. All patients had hematoma within the maxillary sinus, and 47.4% of patients with maxillary sinus trauma were treated conservatively, while 52.6% underwent corrective surgery. The incidence of maxillary sinusitis 3 months post-trauma was 11.6%. Clinical symptoms related to the nasal sinuses included nasal congestion/obstruction (14.7%), nasal discharge (12.6%), reduced/loss of smell (1.1%), and facial pain/pressure (2.1%). Treatment included medical management (54.5%) and endoscopic sinus surgery (45.4%). Conclusion: Maxillary sinus trauma is commonly observed in young individuals, primarily due to traffic accidents, with a higher incidence in males than females. The rate of maxillary sinusitis following trauma is relatively low, and both medical management and surgical intervention are effective when appropriately indicated.